Prospective Relation between Catastrophizing and Residual Pain following Knee Arthroplasty: Two-Year Follow-Up - Michael E Forsythe; Michael J Dunbar; Allan W Hennigar; Michael JL Sullivan; Michael Gross (Pain Research and Management)
BACKGROUND: Pain is the primary indication for both primary and revision total knee arthroplasty (TKA); however, most arthroplasty outcome measures do not take pain into account.